SISTEM INFORMASI PENGELOLAAN TOUR DAN TRAVEL BERBASIS WEB APP PADA CV. KENKEN AGENCY - Khasan Asrori; Solihin Solihin; Istiqomah Rohmawati (Journal of Innovation And Future Technology (IFTECH), 2024)
CV. Kenken is a service company in the city of Serang in managing tour and travel reservations still using the manual system. There are many problems including management of tour booking data and WEB-Based Travel On CV. Kenken Agency, still using a ledger, boking data collection and departure schedule is not well recorded, difficulties in tracking documents sent. The method used is the waterfall method, the design tool uses the UML flow map. While the implementation uses the PHP programming language and MySQL data base. With the web-based tour and travel information system on CV. Kenken Agency, is expected to overcome the problems that exist in the CV. Kenken Agency. Therefore, the recording of documents is neat, the departure schedule is well organized, the latest prices, boking and schedules are well recorded.